Typical or Unique? Polish Adult Interested in K-pop - Sieminska, Dorota (My University, 2023)
This thesis focuses on the topic of Polish K-pop fandom, about which there is still a lack of academic research. The study aims to sketch the figure of an adult person interested in K-pop in Poland and to examine whether it shows features typical for the international K-pop fandom or not. The main research method used is semi-structured interviews conducted with nine adults of Polish nationality interested in K-pop. The essence of the work is three categories distinguished based on data collected during the interviews. The first is the everyday life of people interested in K-pop in Poland, mainly in terms of aspects that can be influenced by K-pop, such as lifestyle, skincare and makeup, clothes, studies, and work, as well as buying and collecting merchandise. The second one is the position of K-pop enjoyer from the perspective of a Polish citizen, where the availability of K-pop content in Poland, as well as the ability to buy related products, plays a key role. Moreover, the visit to Korea is being discussed as a possible factor that may change the experiences on-site in Poland. The third and last category is a discussion on the positive and negative impact that K-pop can have on its audience in Poland, also taking into account the reactions of friends or family to this interest as a potential factor that reduces well-being. The analysis of the interviewees' statements, which cannot be considered a generalization of the entire Polish fandom, shows that people interested in K-pop in Poland seem to be similar to K-pop recipients in other countries in the world but at the same time are different. The informants showed similar characteristics in terms of the impact of K-pop on aspects of everyday life, but being a fan in Poland appears as a limiting factor of the level of K-pop-related experience that this country has, such as organizing concerts and buying albums or other merchandise.
Keywords: K-pop, daily life, fandom, Poland